2017
DOI: 10.1111/cei.13017
|View full text |Cite
|
Sign up to set email alerts
|

Renal-infiltrating CD11c+ cells are pathogenic in murine lupus nephritis through promoting CD4+ T cell responses

Abstract: Lupus nephritis (LN) is a major manifestation of systemic lupus erythematosus (SLE), causing morbidity and mortality in 40-60% of SLE patients. The pathogenic mechanisms of LN are not completely understood. Recent studies have demonstrated the presence of various immune cell populations in lupus nephritic kidneys of both SLE patients and lupus-prone mice. These cells may play important pathogenic or regulatory roles in situ to promote or sustain LN. Here, using lupus-prone mouse models, we showed the pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…This suggests that the combination of pristane and tRA pretreatment may target cDCs in the bone marrow to facilitate glomerulonephritis. This notion is supported by our previous report that activated cDCs from the bone marrow can migrate to the kidney to promote glomerulonephritis in MRL/lpr mice (42). Interestingly, both tRA pre-and post-treatments upon pristane injection significantly expanded the monocytic myeloidderived suppressor cells (MDSCs) gated as Ly6C low/intermediate CD11b + CD11c − compared to pristane alone ( Figure S2A).…”
Section: Enhancement Of Systemic Inflammation By Tra Pre-treatment Insupporting
confidence: 76%
See 1 more Smart Citation
“…This suggests that the combination of pristane and tRA pretreatment may target cDCs in the bone marrow to facilitate glomerulonephritis. This notion is supported by our previous report that activated cDCs from the bone marrow can migrate to the kidney to promote glomerulonephritis in MRL/lpr mice (42). Interestingly, both tRA pre-and post-treatments upon pristane injection significantly expanded the monocytic myeloidderived suppressor cells (MDSCs) gated as Ly6C low/intermediate CD11b + CD11c − compared to pristane alone ( Figure S2A).…”
Section: Enhancement Of Systemic Inflammation By Tra Pre-treatment Insupporting
confidence: 76%
“…Activation of cDCs is required for the induction of glomerular injury and the progression of renal immunopathology in murine models (61,62). Infiltration of activated cDCs into the kidney aggravates the progression of chronic inflammation associated with chronic kidney damage associated with lupus (42,63). Therefore, the results in this study suggest that tRA pre-treatment may have facilitated antigen presentation of apoptotic productswhich are abundant following pristane injection (83)-by MHC-II high cDCs, which subsequently amplified systemic and renal inflammation leading to exacerbated glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…The serum levels of IL-35 were significantly lower in LN patients than SLE patients without nephritis. Previous investigators have reported that chemokines took part in inflammation via attracting T cells in the target organ (Cao et al 2003;Liao et al 2017). Moreover, increased levels of chemokines in SLE were well confirmed (Wong et al 2008;Munroe et al 2017), and might lead to the accumulation of IL-35 in renal tissue.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, we have previously demonstrated that FKN expression was increased in LN model mice and HK-2 cells that were stimulated with lipopolysaccharide, whereas the protein expression of FKN was decreased after methylprednisolone therapy (32). Liao et al reported that anti-CX3CR1 (the receptor of FKN) also can attenuate lupus nephritis in murine model (33).…”
Section: Introductionmentioning
confidence: 99%